Morphologic evaluation of Chinese cervical endplate and uncinate process by three‐dimensional computed tomography reconstructions for helping design cervical disc prosthesis. Issue 9 (September 2016) - Zhu, Yu‐Hang; Cheng, Kai‐Liang; Zhong, Zhuan; Li, You‐Qiong; Zhu, Qing‐San
Abstract : Background : Cervical disc prostheses have been used increasingly in recent years. The successful design of cervical disc prostheses depends on accurate morphometric parameters. However, the morphologic dimensions of the cervical endplate area have not been investigated in the Chinese population. Methods : A total of 1360 cervical endplates and 680 pairs of uncinate processes was retrospectively accessed in 136 Chinese adults. Eleven parameters of each cervical vertebra were measured by three‐dimensional computed tomography reconstructions from C3 to C7. These obtained parameters were compared between sexes, bilateral sides, vertebral segments, and different populations. Results : Five parameters regarding the cervical endplate increased from C3 to C7 in general. Concerning parameters with regard to the uncinate process, the uncinate process distance gradually increased among vertebral segments, and anterior distance was always larger than the posterior distance. The value of left uncinate process angle was on average 0.84° larger than that of the right side, and lower cervical segments had an obviously larger angle. Uncinate process length increased among segments, and no significant difference existed between bilateral sides. Parameters displayed significant difference between sexes. The morphometric parameters of various populations also showed differences. Conclusion : There is a morphologic discrepancy in dimensions of cervical vertebrae regarding sexes, bilateral sides, vertebral segments, and different populations. It is essential to design cervical disc prostheses suited specifically for Chinese patients, for whom the morphometric parameters in our study concerning the cervical endplate and uncinate process can be utilized.